1962
DOI: 10.1121/1.1909139
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Detection Model for Monaural Auditory Detection

Abstract: In the auditory detection of a sinusoidal signal in the presence of random noise, it has previously been demonstrated that the presence of a “pedestal” or background sinusoid of the same frequency and phase as the signal increases detectability. This increase was confirmed in a two-interval forced choice experiment in which a 1000-cps sinusoid was present in one of two 0.1-sec intervals, and the noise plus pedestal were present in both intervals. Pedestals of moderate intensity in phase with the signal increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…In a negative masking paradigm an investigator examines the behavior of DX DL for levels of X close to absolute threshold. The pedestal effect is best demonstrated in plots relating proportion correct to pedestal level (Pfafflin and Mathews, 1962); a plot we call the fixed-signal function. If the level of a signal, DX, is held constant while X varies, and a performance index such as proportion correct is measured, then it has been found that the addition of a pedestal around threshold enables an observer to distinguish the fixed level DX with greater ease than if no pedestal had been present (Green, 1960(Green, , 1966Laming, 1986;Pfafflin and Mathews, 1962).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a negative masking paradigm an investigator examines the behavior of DX DL for levels of X close to absolute threshold. The pedestal effect is best demonstrated in plots relating proportion correct to pedestal level (Pfafflin and Mathews, 1962); a plot we call the fixed-signal function. If the level of a signal, DX, is held constant while X varies, and a performance index such as proportion correct is measured, then it has been found that the addition of a pedestal around threshold enables an observer to distinguish the fixed level DX with greater ease than if no pedestal had been present (Green, 1960(Green, , 1966Laming, 1986;Pfafflin and Mathews, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…The pedestal effect is best demonstrated in plots relating proportion correct to pedestal level (Pfafflin and Mathews, 1962); a plot we call the fixed-signal function. If the level of a signal, DX, is held constant while X varies, and a performance index such as proportion correct is measured, then it has been found that the addition of a pedestal around threshold enables an observer to distinguish the fixed level DX with greater ease than if no pedestal had been present (Green, 1960(Green, , 1966Laming, 1986;Pfafflin and Mathews, 1962). The nonmonotonic form of the fixed-signal function is not accommodated by Weber's law, which stipulates that as X increases the difference between X and XþDX must increase proportionally to maintain a fixed level of performance.…”
Section: Introductionmentioning
confidence: 99%
“…One is the detectability index for an energy detector. In this case, the detector is simply monitoring the energy in a band, W, with noise density, No, and trying to detect a potential signal of energy, E s ' and duration, T Pfaffiin and Mathews (1962) and Green and Swets (1966) have analyzed this case. To a good first approximation…”
Section: Inmentioning
confidence: 98%
“…Historically, however, theoretical predictions of perception have often overestimated the capabilities of the human auditory system. The discrepancies between theorctical and experimcntal results were commonly corrected by adding a Gaussian noise source to the system (e.g., [2]). Howevcr, as this procedure was not physiologically-based, the parameters of the noise sourcc had to be adjusted for each detection problem, reducing the generality of the approach.…”
Section: Introductionmentioning
confidence: 99%
“…+ t t > 0 (2). Since the functional mapping is strictly monotonic, the probability density function can he derived using the formula, where ti = t ; ( y ) and .q'(t;) # 0[ I 11.…”
mentioning
confidence: 99%